ANALISIS KEPUASAN PASIEN RAWAT INAP BANGSAL JANTUNG DI RSUD RADEN MATTAHER JAMBI - Ade Octavia; Suswitaroza -; Aulia Putri Anwar (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
The research aim is to explain and and analysis hospitalized patient satisfaction in Heart Ward and determines strategy to improve quality of service. Data processing is uses servqual gap method instruments. The results shows that generally perception measure shows positive figure though few of them shows negative figure, they are nurse descipline, schedule implementation, situation serenity. These attributes are expected to be the focus of management in delivery service.